Analysis and numerical modelling of ceramic piezoelectric beam behavior under the effect of external solicitations - LEBIED, A.; NECIB, B.; SAHLI, M. (Science des matériaux (Laboratoire LARHYSS), 2017)
The piezoelectric materials have become indispensable in many technological applications. These materials have an inverse piezoelectric effect which allows them to control the form and to present any neither noise nor vibration at any time or position on the structure. In this study we are interested in the bending behavior analysis and modelling of a ceramic beam under external solicitations using numerical simulations based on the finite element methods. The modelling permit to simulate the deformations in a piezoelectric ceramic beam subjected to an electric field and to simple mechanical stress taking into account the electromechanical coupling. It has been found that the obtained analytical results are in a very good agreement with those obtained by numerical modeling. As a result, the interest of such modelling analysis allows the design, the conception and the optimization of mechanical systems based on piezoelectric elements. These materials known as smart or “intelligent” materials, are often used to measure and/or to control finite deformations or vibrations in mechanical systems, so that to prevent their plastic deformations or their total failure.